FRI0149 Comparative risk for hospitalized bacterial infections amoung us veterans with rheumatoid arthritis switching from anti-TNF therapy. (23rd January 2014) - Curtis, J.R.; Yang, S.; Patkar, N.; Chen, L.; Singh, J.; Cannon, G.; Mikuls, T.; Delzell, E.; Saag, K.G.; Safford, M.M.; Duvall, S.; Alexander, K.; et al.
Abstract : Background: Risks of hospitalized infections associated with newer biologic agents have not been well characterized in relation to risks with anti-TNF therapy, especially in rheumatoid arthritis (RA) patients with high comorbidity burdens. Objectives: To compare the risk of hospitalized infections among RA patients switching from anti-TNF therapy to rituximab (RTX), abatacept (ABA) or another anti-TNF. Methods: Using data from 2002-10 from the U.S. Veteran's Health Administration, we identified a cohort of 38453 RA patients. Eligible patients started RTX, ABA, or anti-TNF therapy after prior exposure to another anti-TNF agent. To minimize confounding from channeling of cancer patients to certain biologics, patients with a history of cancer were excluded to form 2 cohorts: Exclusion for any type of prior cancer using all available data (3257 episodes, 2559 patients) or exclusion only for hematologic cancer in the prior 12 months (3848 episodes, 3018 patients). Baseline characteristics defined in 1 year prior to treatment initiation. Exposure was as-treated based upon days supply (injections) or usual dosing intervals (infusions), with 12 months assumed for RTX exposure. Current exposure was extended by 90 days for all biologics. The outcome was hospitalization with primary diagnosis code for bacterial infection. The hazard ratio (HR, 95% CI) for infection for RTX and ABA vs. anti-TNFs was calculated, adjusting for multiple potential confounders. Results: 523 RTX, 366 ABA and 2959 anti-TNF switcher episodes were identified in RA patients without hematologic cancers; 15% of treatment episodes were further excluded with the more restrictive cancer exclusion to form a 2nd cohort. This cohort's mean overall age was 60.8±10.7 years, 87% male, 25% diabetes, 15% COPD, 3% heart failure, and 66% used glucocorticoids. 2/3rd of the anti-TNF exposure was adalimumab. The most common types of hospitalized infections were pneumonia (36%), skin/soft tissue infections (26%), gastroenteritis (7%) and urinary tract infections (6%). In the less restrictive RA cohort, crude hospitalized infection rates/100person years were RTX: 15.9, ABA: 10.2 and anti-TNF: 12.7. In the less restrictive RA cohort, adjusted HRs for infection were comparable to or lower than for anti-TNF therapy: RTX: 0.85 (0.62-1.12) and ABA: 0.72 (0.50-1.10). In the more restrictive RA cohort, results were similar: adjusted HR for RTX: 0.76 (0.50-1.15) and ABA: 0.58 (0.36-0.93) compared to anti-TNF therapy. Multiple comorbidities and medications were associated with infections (diabetes HR=1.4, 95% CI 1.1-1.7; chronic lung disease HR=1.5, 1.1–1.9; prednisone >7.5mg/day HR=2.1, 1.6-2.7). Conclusions: In older, predominantly male, US veterans with RA and high comorbidities, risks of hospitalized bacterial infections for patients treated with RTX or ABA were comparable to or lower than for patients switching to a different anti-TNF therapy (mostly ADA). Ongoing work is characterizing the comparative risks of opportunistic infections. Disclosure of Interest: J. Curtis Consultant for: Roche/Genetech, UCB, Centocor CORRONA, Amgen, Pfizer, BMS, Crescendo, Abbott, S. Yang: None Declared, N. Patkar: None Declared, L. Chen: None Declared, J. Singh Grant/Research support from: Takeda, Savient, Consultant for: URL pharmaceuticals, Takeda, Ardea, Savient, Allergan, Novartis, G. Cannon: None Declared, T. Mikuls: None Declared, E. Delzell Grant/Research support from: Amgen, K. Saag Consultant for: Amgen; Lilly; Merck; Novartis; Savient; Ardea; Regeneron; URL, Abbott; DSMB – BioCryst; Roche; Lilly, M. Safford: None Declared, S. Duvall Grant/Research support from: Anolinx, LLC, Genentech, Roche, Amgen, Shire, K. Alexander Employee of: Genetech, P. Napalkov Employee of: Genetech, A. Kamauu Employee of: President- Anolinx LLC, J. Baddley Consultant for: Abbott, Merck